Christian Trade Unionism in France: A Left Socialist Experience - Kassalow, E. (Relations industrielles / Industrial Relations, 1977)
The author présents a synthesis of the évolution of the Confédération française démocratique du travail. The French Démocratie Confédération of Labor.